2021
DOI: 10.1108/jmtm-06-2020-0247
|View full text |Cite
|
Sign up to set email alerts
|

Understanding lead-time implications for financial performance: a qualitative study

Abstract: PurposeThe purpose of the study is to describe the implications of strategic lead times (SLTs) for return on investment (ROI).Design/methodology/approachThis study was part of an interactive research project and is based on the logic of theory application leading to theory building. It uses a multiple case study with five holistic single cases. Empirical data (ED) have mainly been collected from interviews and focus groups.FindingsThe length of and uncertainty in SLTs have implications for companies' financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Jayaram et al [34] determined that financial performance is strongly related to competitive lead-time, based on a study of three car manufacturers in North America. Tiedemann et al [35] confirmed this based on multiple case studies.…”
Section: Effect Of Production Costs On Decision Variablesmentioning
confidence: 80%
“…Jayaram et al [34] determined that financial performance is strongly related to competitive lead-time, based on a study of three car manufacturers in North America. Tiedemann et al [35] confirmed this based on multiple case studies.…”
Section: Effect Of Production Costs On Decision Variablesmentioning
confidence: 80%
“…Imoisili (1978), studying indigenous and multinational companies in Nigeria, concluded that the more effective companies are found among organizations which maintain consistency between environmental perception and management practices, do longterm planning, use more flexible control systems and have shorter lead time. Fubara (2006) did a survey in Nigeria and observed that companies that have efficient lead time experienced growth in profits Tiedemann, Wikner & Johansson (2021). investigated Understanding lead-time implications for financial performance: a qualitative study.…”
mentioning
confidence: 99%